2017
DOI: 10.1093/nar/gkx235
|View full text |Cite
|
Sign up to set email alerts
|

Identification and dynamic changes of RNAs isolated from RALY-containing ribonucleoprotein complexes

Abstract: RALY is a member of the heterogeneous nuclear ribonucleoprotein family (hnRNP), a large family of RNA-binding proteins involved in many aspects of RNA metabolism. Although RALY interactome has been recently characterized, a comprehensive global analysis of RALY-associated RNAs is lacking and the biological function of RALY remains elusive. Here, we performed RIP-seq analysis to identify RALY interacting RNAs and assessed the role of RALY in gene expression. We demonstrate that RALY binds specific coding and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 95 publications
2
46
0
Order By: Relevance
“…Interestingly, E2F1 and E2F2 mRNAs were identified previously as specific targets of RALY in the RIP-seq experiment performed in MCF7 cells, whereas all the proliferation repressors of the E2F family were not detected as RALY RNA interactors (Fig. 3B) (32).…”
Section: Raly Binds E2f1 Mrna and Regulates Its Stabilitymentioning
confidence: 68%
See 4 more Smart Citations
“…Interestingly, E2F1 and E2F2 mRNAs were identified previously as specific targets of RALY in the RIP-seq experiment performed in MCF7 cells, whereas all the proliferation repressors of the E2F family were not detected as RALY RNA interactors (Fig. 3B) (32).…”
Section: Raly Binds E2f1 Mrna and Regulates Its Stabilitymentioning
confidence: 68%
“…To have a more comprehensive understanding of the general function of RALY on its target mRNAs, we intersected the list of differentially expressed genes detected in HeLa cells with the list of RALY targets identified previously by RIP-seq in MCF7 cells (32). We found that 193 up-regulated genes and 359 downregulated genes were present in both lists (Fig.…”
Section: The Down-regulation Of Raly Impairs the Expression Of Cell Cmentioning
confidence: 94%
See 3 more Smart Citations